Genetic relationship between local guinea fowl, quail and chicken using RAPD–PCR technique - Hurea Abdulrazaq; Questan Ameen (Mesopotamia Journal of Agriculture)
This study combines three of the most common bird species in both Iraq and the rest of the globe. This type of study demonstrates the degree of genetic convergence between these species. Blood samples from chicken, Guinea fowl, and quail were used in this study.  The Four hundred and fifty birds are divided into 150 birds per species. Blood from a bird was sampled.  The DNA samples' purities varied from 1.8 to 1.9. the (22) Gen Script USA primers are used. Overall, all of the primers produced (340) bands, 95 of which were polymorphic, with the maximum number of bands belonging to the OPA-20 and the lowest number of bands to the OPA-13. OPA-12 had the highest percentage (50.0), though. Primer OPA-20 has the widest molecular weight range (100- 1500 bp). Guinea fowl have a greatest number of bands overall (131), while quail reported the highest polymorphic bands overall (12) and polymorphism percentage (11.8). The maximum genetic similarity is found between chicken and quail (0.608), it is obvious that the genetic differences between the three groups are greatest between the Guinea fowl, quail and smallest between the quail and the chicken.